Skeptical theism and the challenge of atheism - Sterba, James P. (International journal for philosophy of religion, 2019)
Skeptical theists hold that we should be skeptical about our ability to know the reasons that God would have for permitting evil, at least in particular cases. They argue for their view by setting aside actions that are wrong in themselves and focusing their attention on actions that are purportedly right or wrong simply in terms of their consequences. However, I argue in this paper that once skeptical theists are led to take into account actions that are wrong in themselves, as they must, they cannot escape the conclusion that there is a logical contradiction between the existence of an all-good, all-powerful God and what would have to be God's permission of the significant and horrendous evil consequences of immoral actions found in our world.